Unlocking the Silences of the Self-Murdered: Textual Approaches to Suicidal Emotions in the Middle Ages. (2014) - F. McNamara, Rebecca; Feros Ruys, Juanita
<x content-type="archive" xml:space="preserve">Abstract</x> What emotions did people in the Middle Ages associate with suicide, and how did they react emotionally to the possibility or act of suicide? Although pre-modern Europe did not have a dedicated word to signify the concept of self-inflicted death, and although there is no evidence of suicide notes until the seventeenth century, we find in a range of medieval texts an interest in the act and attendant emotions of suicide. In this essay, we demonstrate how scholars might discover emotions related to suicide in two genres: English legal records and first-person life narratives. Through close attention to textual detail and recourse to wider cultural implications of emotionally meaningful contexts, we show that even the unlikeliest of texts can provide inroads to emotions related to medieval suicide. With these models we hope to encourage scholars to seek other genres and ways of reading that will help to unlock the silences of the self-murdered.